Richelieu's army : war, government, and society in France, 1624-1642 - Parrott, David (Cambridge studies in early modern history., 2001)
It is assumed widely that 'war made the state' in seventeenth-century France. Yet this study challenges the traditional interpretations of the role of the army as an instrument of the emerging absolutist state, and shows how the expansion of the French war effort contributed to weakening Richelieu's hold upon France. Runner up in the History Today Awards 2002.